Ethanol extract of propolis relieves exercise-induced fatigue via modulating the metabolites and gut microbiota in mice - Huang, Shan; Yang, Xiaofei; Ma, Jingxuan; Li, Chen; Wang, Yajing; Wu, Zhaoxia (Frontiers in Nutrition, 2025)
BackgroundPropolis, a natural mixture rich in bioactive compounds, has shown the potential to relieve exercise-induced fatigue. However, the underlying mechanism remains unclear. This study aimed to explore the anti-fatigue effects of ethanol extract of propolis (EEP) and its potential mechanisms.MethodsMale C57BL/6 mice aged 6–8 weeks were subjected to swim training with or without EEP supplementation (400 mg/kg.bw) for 3 weeks, followed by a exhaustive swimming test to simulate exercise-induced fatigue. The exhaustion time and fatigue-related biochemical indices were measured to assess the anti-fatigue effects. The anti-fatigue mechanism of EEP was further investigated using untargeted serum metabolomics and 16S rRNA gene sequencing of the gut microbiota.ResultsThe results showed that supplementation with EEP significantly increased the exhaustive swimming time of the mice by 27.64%, with no significant effects on body weight, food intake, or viscera and muscle index among the 3 groups. Biochemical analysis indicated that EEP effectively alleviated fatigue-related biochemical indices caused by excessive exercise, including liver glycogen (LG), muscle glycogen (MG), blood lactate (BLA), blood urea nitrogen (BUN), lactate dehydrogenase (LDH), interleukin-6 (IL-6), interleukin-1β (IL-1β), tumor necrosis factor-alpha (TNF-α), superoxide dismutase (SOD), total antioxidant capacity (T-AOC), glutathione peroxidase (GSH-Px), and malondialdehyde (MDA). Serum metabolomics analysis revealed that EEP reversed the levels of 6 key metabolites (Gamma-Aminobutyric acid, pipecolic acid, L-isoleucine, sucrose, succinic acid, and L-carnitine), which are involved in 7 metabolic pathways related to energy metabolism, amino acid metabolism, and carbohydrate metabolism. 16S rRNA sequencing analysis of the cecal contents showed that EEP altered the composition and structure of the gut microbiota, increasing the abundance of butyrate-producing bacteria and reducing the abundance of harmful bacteria. Correlation analysis revealed that specific bacterial genera were closely related to certain differential metabolites and biochemical indices.ConclusionOur study showed that EEP significantly increased exercise endurance in mice and exerted anti-fatigue effects by modulating key metabolites and the gut microbiota.